2014
DOI: 10.4081/reumatismo.2014.758
|View full text |Cite
|
Sign up to set email alerts
|

Physiopathology of pain in rheumatology

Abstract: summary Pain is the main manifestation of many rheumatic diseases (be they overtly inflammatory such as rheumatoid arthritis or dysfunctional such as fibromyalgia) but, at least initially, the mechanisms involved in the genesis, amplification and chronicisation of the persistent pain characterising the various conditions can be very different. The main peripheral mechanism underlying acute nociceptive pain is a change in the activity of the nociceptors located in the affected anatomical structures (joints, ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…At that basis, peripheral pain generators likely play some role, but probably through CNS activation, which becomes largely independent of peripheral nociceptive input [ 21 ]. Finally, a potential mechanism that could explain the acute nociceptive pain in FM, is a change in the activity of the nociceptors located in the affected anatomical structures (joints, tendons, and ligaments), which augments their sensitivity sensitive to normally painful stimuli (hyperalgesia), or normally non-painful stimuli (allodynia) [ 33 ].…”
Section: Fibromyalgiamentioning
confidence: 99%
“…At that basis, peripheral pain generators likely play some role, but probably through CNS activation, which becomes largely independent of peripheral nociceptive input [ 21 ]. Finally, a potential mechanism that could explain the acute nociceptive pain in FM, is a change in the activity of the nociceptors located in the affected anatomical structures (joints, tendons, and ligaments), which augments their sensitivity sensitive to normally painful stimuli (hyperalgesia), or normally non-painful stimuli (allodynia) [ 33 ].…”
Section: Fibromyalgiamentioning
confidence: 99%
“…Neurophysiological changes compatible with central sensitization are now recognized in understanding chronic pain in rheumatoid conditions, such as rheumatoid arthritis, osteoarthritis and fibromyalgia (38). Several studies have found EDS to have close resemblance with fibromyalgia as both conditions are characterized by pain, fatigue and physical disability (4,9).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the total score for each of the five subscales of SHC, a mean score was calculated (38). For each of the eight items of B-IPQ a mean group value was calculated.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Until a few years ago, the pain associated with many rheumatic diseases was considered to be peripheral in origin and induced by the well-known mechanisms of acute or chronic inflammation, or morpho-structural alterations in the involved joints [37,38]. However, the mechanisms underlying chronic widespread pain (the prototype of which is FM) have only recently been identified as neurophysiological modifications in the perception, transmission and, above all, processing of nociceptive afferents at the level of the CNS, which seem to be caused by what has come to be called "sensitisation": i.e.…”
Section: Sle and Central Painmentioning
confidence: 99%